CLINICAL AND BIOCHEMICAL ASPECTS OF THE USE OF MAGNESIUM IN OBSTETRICS, GYNECOLOGY AND PERINATOLOGY - K. Dadak; A. D. Makatsariya; D. V. Blinov; U. V. Zimovina (IRBIS LLC, 2016)
Significant biochemical role of magnesium in the body is well-known, as well as good proven clinical efficacy of magnesium in obstetrics and gynecology. Magnesium preparations, in particular magnesium sulfate, are recommended as the treatment of choice for premature birth, pre-eclampsia and eclampsia. There is evidence and its neuroprotective effects on the fetus. Restricts the use of magnesium sulfate possibility of overdose with serious side effects. Reduce the risk of overdose can be minimized using standard protocols, independent double-check, monitoring the patient'scondition. Magnesium sulfate therapy, as a means of emergency, cannot compensate for a deficiency of magnesium, which is associated with the development of obstetric pathologies such as threatened miscarriage, premature birth, placental insufficiency, preeclampsia, thrombophilia, premenstrual syndrome (PMS), the appointment of combined oral contraceptives (COCs) and hormone replacement therapy (HRT), climacteric syndrome. Justified use of organic salts of magnesium orally - along with better bioavailability they do not lead to serious side effects in overdose. Using organicmagnesium salts to control magnesium deficiency and related symptoms is also shown at the ICP, and the appointment of COCs HRT during menopause. The use of magnesium citrate is the most preferred because citrate anion causes high bioavailability of magnesium, it is also required in the Krebs cycle and recycled into carbon dioxide and water. Thismakes it an ideal transporter of magnesium into cells.